Impact of multicenter unified enhanced environmental cleaning and disinfection measures on nosocomial infections among patients in intensive care units. Issue 8 (August 2020) - Huang, Jing; Cui, Can; Zhou, Shuli; Chen, Ming; Wu, Hao; Jin, Ronghua; Chen, Xinyue
Objectives: Most Chinese hospitals have customized environmental cleaning policies and systems, with limited data availability based on evidence-based medicine. This study investigated the relationship between multidrug-resistant organism (MDRO) colonization in intensive care unit (ICU) patients and ICU surface bacterial contamination status. Methods: This cross-sectional study comprised MDRO screening in ICU patients using bacterial cultivation by chromogenic medium; samples were collected before (control group) and after implementation of enhanced cleaning (cleaning group). Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry was used to identify and analyze microorganisms; the relationships of MDRO colonization with infection and environmental bacteria were analyzed. Results: In total, 196 patients were enrolled in the study (104 and 92 in control and cleaning groups, respectively); 1042 MDROs were subjected to screening before and after cleaning. After cleaning, the rate of MDRO detection on surfaces of frequently touched objects in ICUs decreased from 31.77% to 13.32%. There were fewer MDRO homologues in the cleaning group than in the control group. Moreover, the cleaning group had a shorter ICU stay and significantly lower mortality rate. Conclusions: Enhanced environmental cleaning and disinfection could reduce environmental MDRO accumulation and suppress MDRO colonization in ICUs, thereby reducing nosocomial infections and improving adverse patient outcomes.